2021
DOI: 10.1186/s13148-021-01025-5
|View full text |Cite
|
Sign up to set email alerts
|

FK228 sensitizes radioresistant small cell lung cancer cells to radiation

Abstract: Background Concurrent thoracic radiation plus chemotherapy is the mainstay of first-line treatment for limited-stage small cell lung cancer (LS-SCLC). Despite initial high responsiveness to combined chemo- and radiotherapy, SCLC almost invariably relapses and develops resistance within one year, leading to poor prognosis in patients with LS-SCLC. Developing new chemical agents that increase ionizing radiation’s cytotoxicity against SCLC is urgently needed. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…This is in line with earlier published data by Jin et al [ 19 ] who showed a slightly increased radiosensitivity upon treatment of BON-1 and QGP-1 cells with CI-994. Similar results were demonstrated for several other cancer types [ 30 , 31 , 32 , 33 ]. This suggests that VPA may have a dual function; it increases both SSTR2 mRNA expression levels and uptake of [ 111 In]In-DOTATATE, and it increases radiosensitivity towards PRRT.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with earlier published data by Jin et al [ 19 ] who showed a slightly increased radiosensitivity upon treatment of BON-1 and QGP-1 cells with CI-994. Similar results were demonstrated for several other cancer types [ 30 , 31 , 32 , 33 ]. This suggests that VPA may have a dual function; it increases both SSTR2 mRNA expression levels and uptake of [ 111 In]In-DOTATATE, and it increases radiosensitivity towards PRRT.…”
Section: Discussionsupporting
confidence: 87%
“…As MRE11 and NBS1 deficiencies sensitize human cancer cells to etoposide (Hoa et al, 2016), it is worth investigating combination with etoposide and the MRE11 endonuclease inhibitors (PFM 01 and 03) in cancer cell lines as well as tumor xenograft models with different MRE11 expressions. For example, chemo-and radio-resistant small cell lung cancer (SCLC) cells display a higher expression of the MRN complex (Li et al, 2021), targeting MRE11 using PFM 01/03 could potentially improve the response of these cells to etoposide, a key component of the first-line therapy for SCLC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, increasing evidence has documented that HDAC inhibitors improve radiosensibility in malignancies, including lung cancer, colon cancer, glioma and squamous cell carcinoma [ 28 – 31 ], suggesting the implication of HDACs in tumor radiation resistance. For instance, HDAC4 and HDAC6 have been indicated to make glioma cells resistant to radiation by maintaining DNA double-strand damage repair and stemness [ 6 ].…”
Section: Discussionmentioning
confidence: 99%